2023
DOI: 10.1186/s10194-023-01600-6
|View full text |Cite
|
Sign up to set email alerts
|

SS-31 alleviated nociceptive responses and restored mitochondrial function in a headache mouse model via Sirt3/Pgc-1α positive feedback loop

Zhengming Shan,
Yajuan Wang,
Tao Qiu
et al.

Abstract: Migraine is the second highest cause of disability worldwide, bringing a huge socioeconomic burden. Improving mitochondrial function has promise as an effective treatment strategy for migraine. Szeto-Schiller peptide (SS-31) is a new mitochondria-targeted tetrapeptide molecule that has been shown to suppress the progression of diseases by restoring mitochondrial function, including renal disease, cardiac disease, and neurodegenerative disease. However, whether SS-31 has a therapeutic effect on migraine remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that ROS, key molecules involved in oxidative stress, play pivotal roles in synaptic plasticity and neuronal excitability ( Bittar et al, 2017 ; Esteras et al, 2022 ). Shan et al (2023) reported that the levels of ROS was elevated in a mouse model of IS-induced headache. Consistent with their study, we also found increased ROS levels in a rat model of CM induced by IS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ROS, key molecules involved in oxidative stress, play pivotal roles in synaptic plasticity and neuronal excitability ( Bittar et al, 2017 ; Esteras et al, 2022 ). Shan et al (2023) reported that the levels of ROS was elevated in a mouse model of IS-induced headache. Consistent with their study, we also found increased ROS levels in a rat model of CM induced by IS.…”
Section: Discussionmentioning
confidence: 99%